Сорокопутовый свиристель (Hypocolius ampelinus) (Aves, Bombycillidae) — гнездящийся вид фауны СССР - Пекло, А.М.; Сопыев, О.С. (Вестник зоологии, 1980)
Hypocolius ampelinus B o n a p., which had been considered a rare stray species of the USSR fauna, was recorded first for the USSR territory in May-June 1979 in the nesting place in the Middle Murghab river tugais (Turkmen SSR, environs of the Takhta-Bazar town). Six found nests, clutches, downy nestlings, nest life of this species are described. Hypocolins ampelinus B o n a p. is recommended to be included to the Red data book of the USSR. This species and places of its nesting need protection in the USSR territory.